Best Answer

Related Post

Spread the word

Digg this post

Bookmark to delicious

Stumble the post

Add to your technorati favourite

Subscribes to this post

6 Comments Already

mygif
l_town_51 Said,
January 25th, 2011 @8:55 am  

use the quadradtic equation. -b +- sqrt( b^2 -4ac) / 2a

4 = a
0 = b
-8 = c

mygif
Davis P Said,
January 25th, 2011 @9:51 am  

4x^2 – 8 = 0
x^2 = 2
x = +/- sqrt(2)

mygif
Tony D Said,
January 25th, 2011 @10:10 am  

why are you using quadratic formula? just use, dare i say it – your brain.

mygif
jen m Said,
January 25th, 2011 @10:50 am  

4x^2=8
x^2=2
x= plus or minus square root of 2

mygif
yapsterr2 Said,
January 25th, 2011 @11:33 am  

(0 +- sqroot(0 – (4)(4)(-8))) / (4)(2)

+- 8sqroot(2)/8

the answer is sqroot of 2

mygif
grampedo Said,
January 25th, 2011 @12:01 pm  

4x^2-8=0
4(x^2-2)=0
Divide both sides by 4
x^2-2=0
x^2=2
x= +/- sq.rt.(2)
If you were to use the quadratic formula,
4x^2-8=0 should be re-written as
4x^2+0x-8=0
a=4, b=0, c= -8
x= {-b+/-rt(b^2-4ac)} / 2a
x= {0+/-rt(0-4(4)(-8)} / 8
x={+/-rt(128)} / 8
x= +/-{rt(64)rt(2)} / 8
x= +/-8rt(2)/8
x= +rt(2) or -rt(2)

Leave Your Comments Below

Please Note: All comments will be hand modified by our authors so any unsuitable comments will be removed and you comments will be appreared after approved